Behaviour of Individual Investors in Stock Market: How Bias Affect on Decision Making - Asha Salsabila; Kusumaningtyas, Rohmawati (International Environmental Conferrence on Biosustainability Advancement, 2024)
The capital market has become a popular investment destination, this can be seen in the growth of investment in Indonesia. Investment growth in Indonesia has increased significantly, with the proven increase in the number of Single Investor Identification (SID). Before determining an investment decision, you have to consider a lot. There are many factors that influence investment decision making, including biased psychological factors that can make investors irrational. Therefore, the purpose of this study is to find out the effects of bias, namely self-attribution bias, overconfidence bias, and herding bias on investment decision making. The sample in this study were students of the Faculty of Economics and Business in East Java because students represented potential young investors to contribute in investing in the capital market. Respondents in this study were 200 respondents and data were processed using SPSS Statistics 24. Questionnaires were distributed online and tested for multiple regression. The results of this study are self-attribution bias overconfidence bias, and herding bias have positive effects on investment decision making. The high self-attribution bias can cause investors to make mistakes in interpreting the information obtained regarding the investments made. Then, impact of this overconfidence can affect investors in the way they exaggerate their ability to assess a company’s potential as an investment destination, tend to take excessive risks when trading, and underestimate existing risks. Last one is herding, investors advised to be more careful in making decisions because biased herding behavior can have a negative impact on the investment decisions taken.